Toward Standardized Musculoskeletal Ultrasound in Pediatric Rheumatology: Normal Age‐Related Ultrasound Findings. Issue 3 (March 2016) - Collado, Paz; Vojinovic, Jelena; Nieto, Juan Carlos; Windschall, Daniel; Magni‐Manzoni, Silvia; Bruyn, George A. W.; Iagnocco, Annamaria; D'agostino, Maria Antonietta; Naredo, Esperanza; ,
Abstract : Objective: The Outcome Measures in Rheumatology Ultrasound Task Force has recently started to work on the validation and standardization of musculoskeletal ultrasound (MSUS) examination in children in order to improve its applicability to joint examination. Methods: This was a prospective multicenter study performed by 4 experts in pediatric MSUS, who independently collected representative images using predefined scanning procedures of 4 joints (knee, ankle, wrist, and second metacarpophalangeal joint) in different predefined age groups. Researchers were allowed to use their own settings (B‐mode and Doppler) in order to get the best quality image and highest sensitivity for low blood flow. Images were evaluated for quality parameters and an atlas was created with the best images. An equipment comparative study was performed by a single examiner using 2 different types of machines. Results: Sixty‐four healthy children were scanned. The quality of evaluated images, obtained by predefined scanning positions, was highly comparable among the examiners. The B‐mode images clearly showed age‐related variations of joint findings, while Doppler images showed the presence of blood flow, particularly within the epiphyseal cartilage of the children at a younger age. There was a high to good level of consistency between images obtained from the 2 different ultrasound machines. Conclusion: The study shows a systematic method for ultrasound examination of children at different age groups. Additionally, a baseline collection of images was developed, showing blood vessels in the joints examined. The present study could provide a framework for ongoing MSUS studies as well as for clinical practice in pediatric rheumatology.